Mass Spectrometry-Based System for Identifying and Typing Norovirus Major Capsid Protein VP1 - Pei-Yu Chu; Hui-Wen Huang; Michittra Boonchan; Yu-Chang Tyan; Kevin Leroy Louis; Kun-Mu Lee; Kazushi Motomura; Liang-Yin Ke (Viruses, 2021)
Norovirus-associated diseases are the most common foodborne illnesses worldwide. Polymerase chain reaction-based methods are the primary diagnostics for clinical samples; however, the high mutation rate of norovirus makes viral amplification and genotyping challenging. Technological advances in mass spectrometry (MS) make it a promising tool for identifying disease markers. Besides, the superior sensitivity of MS and proteomic approaches may enable the detection of all variants. Thus, this study aimed to establish an MS-based system for identifying and typing norovirus. We constructed three plasmids containing the major capsid protein VP1 of the norovirus GII.4 2006b, 2006a, and 2009a strains to produce virus-like particles for use as standards. Digested peptide signals were collected using a nano-flow ultra-performance liquid chromatography mass spectrometry (nano-UPLC/MSE) system, and analyzed by ProteinLynx Global SERVER and TREE-PUZZLE software. Results revealed that the LC/MSE system had an excellent coverage rate: the system detected more than 94% of amino acids of 3.61 femtomole norovirus VP1 structural protein. In the likelihood-mapping analysis, the proportions of unresolved quartets were 2.9% and 4.9% in the VP1 and S domains, respectively, which is superior to the 15.1% unresolved quartets in current PCR-based methodology. In summary, the use of LC/MSE may efficiently monitor genotypes, and sensitively detect structural and functional mutations of noroviruses.